Priming involuntary autobiographical memories in the lab - Barzykowski, Krystian; Niedźwieńska, Agnieszka (Memory (Hove), 2018)
Involuntary autobiographical memories (IAMs) are recollections of personal past that frequently and spontaneously occur in daily life. Initial studies by Mace (2005) showed that deliberately reminiscing about a certain lifetime period (e.g., high school) significantly increased the number of different IAMs from the same period in subsequent days, suggesting that priming may play a significant role in the retrieval of IAMs in everyday life. In the present study, we used a modified experimental paradigm, originally used by Schlagman and Kvavilashvili (2008), to study IAMs under well-controlled laboratory conditions. Participants completed a monotonous vigilance task twice and reported the occurrence of any spontaneous thoughts that were later classed as IAMs or other thoughts. Priming was manipulated by having experimental participants reminiscing about high school period between the two vigilance tasks and control participants playing simple games. Results showed that participants in the experimental group reported IAMs relating to high school period more frequently during the second vigilance task than those in the control group. In the experimental group, the number of high school memories was marginally higher in the second vigilance task compared to the first vigilance task with the medium effect size, but this within subjects effect was not significant in the control group. Finally, priming also enhanced the retrieval of more remote IAMs in the experimental group compared to the control group. These results suggest that priming may play a significant role in the activation and recall of IAMs and open up interesting avenues for future research.